In Vivo Measurements Reveal Increased Nucleus Pulposus Lactate and Oxygen Concentrations in a Goat Model of Intervertebral Disc Degeneration - Karthikeyan Rajagopal; Thomas P. Schaer; Kyle D. Meadows; Madeline Boyes; Rachel Hilliard; John C. O'Donnell; George R. Dodge; Dmitriy Petrov; Dawn M. Elliott; Robert L. Mauck; Lachlan J. Smith; Neil R. Malhotra (JOR Spine)
ABSTRACT Introduction Intervertebral disc degeneration is strongly implicated as a cause of low back pain. Although the precise pathophysiological mechanisms remain elusive, perturbations in nutrition that adversely impact the cellular microenvironment of the central nucleus pulposus (NP) may be contributing factors. A comprehensive understanding of this microenvironment, including changes in nutrient availability as a function of degeneration, is critical for the development of effective cell‐based treatments. The goal of this study was to adapt brain tissue oxygen probes and microdialysis catheters for in situ determination of relative NP oxygen, glucose, and lactate levels in a preclinical goat model of disc degeneration. Methods Following ex vivo technical refinement in bovine caudal discs, baseline metabolite measurements were performed in vivo in the lumbar discs of 3 large frame goats. Degeneration was then induced via injection of chondroitinase ABC (ChABC) into the NP, and measurements were repeated after 12 weeks. Degeneration severity was graded using magnetic resonance imaging (MRI) and histology, and vertebral endplate porosity was assessed using microcomputed tomography. Results Oxygen and lactate levels in goat NPs were significantly higher in degenerate compared to healthy discs, while glucose levels were not significantly different. ChABC‐injected discs exhibited higher vertebral endplate porosity, worse histological and MRI grades, and a spectrum of cartilage endplate damage compared to healthy discs. There were significant positive correlations between MRI grade and both NP oxygen and lactate levels. Discussion We successfully adapted techniques including surgical placement, equilibration time, flow rate, and detection method for in situ measurement of oxygen, glucose, and lactate in a goat model of disc degeneration. Interestingly, while increased lactate with degeneration was expected, increased oxygen levels were unexpected. Our findings may, in part, be explained by associated alterations in disc and endplate structure, and motivate future studies to comprehensively establish the underlying mechanisms in this model.